World Bank Economists' Forum : Volume 1 - Devarajan, Shantayanan; Rogers, F. Halsey; Squire, Lyn (Washington, DC: World Bank, 2013)
The first World Bank Economists' Forum was held on May 3-4, 1999. The forum attempts to answer these questions: How do you recognize a hidden fiscal crisis? When capital flows are volatile, what types of policy announcements can help fend off currency crises? Do government training programs for unemployed workers have an effect? What infrastructure investments reduce infant mortality? This book collects nine outstanding papers presented at the forum. The main theme surveyed in this book include fiscal policy, capital flows, trade, decentralization, labor markets, infrastructure, health, and worker training. The second volume collects eight more papers, concerned with household behavior and health, communities and welfare, local governments and basic services, and firms and governments under uncertainty.